The performance of osteoporosis self-assessment tool for Asians (OSTA) in assessing the risk of osteoporosis in postmenopausal women aged 45 years and older - Tran, Hoang Hoa Nhien; Nguyen, Hoang Thanh Van; Le, Thi Hong Van; Truong, Huu Hung (Tạp chí Y Dược Huế, 2024)
Objectives: Application of the OSTA (Osteoporosis Self-Assessment Tool for Asians) in assessing the risk of osteoporosis in postmenopausal women aged 45 years and older; Evaluation of the relationship between OSTA and bone mineral density measured by dual-energy X-ray absorptiometry (DEXA). Subjects and methods: A cross-sectional descriptive study was performed on 430 postmenopausal women aged 45 years and older who were treated at Hue University of Medicine and Pharmacy Hospital from 9/2021 to 6/2022. Bone mineral density was measured by dual-energy X-ray absorptiometry (DEXA). Diagnosis and classification of osteoporosis are based on the T-score (WHO 1994). Calculating the OSTA according to the formula: OSTA = 0.2 x [weight (kg) - age (years)]. Results: The average OSTA value is -2.97 ± 3.35, the minimum value is -12.8, and the maximum value is 7.0. Osteoporosis risk ratios according to the OSTA (using cut-offs 0 and -3) were: high risk (46.1%), moderate risk (35.3%), and low risk (18.6%). The predictive value of osteoporosis risk of the OSTA was ranked as good with the area under the curve (AUC) of 0.823 (p < 0.001). At cut-off -3, the OSTA has a sensitivity of 70.3%, and a specificity of 78.4%. At cut-off 0, the OSTA has a sensitivity of 96.8%, and a specificity of 33.1%. The prevalence of osteoporosis in the high-, intermediate- and low-risk groups (using cut-offs 0 and -3) was 69.2%, 28.3%, and 6.3%, respectively. Conclusion: OSTA can be used as a simple and convenient tool for self-assessment or screening for osteoporosis risk